Islamic Religious Education Teachers' Creativity in Using Learning Media to Improve Student Achievement at SMP Negeri 1 Rantau Selamat - Andriani Andriani; Basri Ibrahim; Lathifah Hanum (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
The objectives of the research are: 1). To analyze the ability of Islamic Education (PAI) teachers in the use of learning media to improve student achievement at SMP Negeri 1 Rantau Selamat. 2). To analyze the ability of PAI teachers in selecting appropriate learning media to improve student achievement at SMP Negeri 1 Rantau Selamat. 3). To analyze the improvement of student achievement at SMP Negeri 1 Rantau Selamat. The research method used is qualitative research of the field research type. Data collection was carried out through observation, interviews, and documentation. The results of the study show that: 1). PAI teachers at SMP Negeri 1 Rantau Selamat have fairly good ability in utilizing learning media, both in the form of visual, audio, and simple technology media. The use of these media can increase students’ attention, understanding, and involvement in the learning process. 2). PAI teachers are able to adjust learning media to the characteristics of the material, students’ conditions, and learning objectives. Varied media such as PowerPoint, animated videos, puzzle cards, and practice-based learning have proven effective in increasing classroom interaction and students’ learning motivation. 3). Students’ achievement at SMP Negeri 1 Rantau Selamat has improved in academic aspects, religious behavior, and learning motivation. The academic scores of the PAI subject show a significant increase; students’ religious behavior has improved, marked by increased discipline in worship and participation in religious activities; and students’ intrinsic and extrinsic motivation toward learning has also increased